Challenges to the learning organization in the context of COVID-19 pandemic uncertainty: creativity – based response - Vainauskienė, Vestina; Vaitkienė, Rimgailė (Creativity Studies, 2022)
The COVID-19 pandemic poses several challenges transforming the learning organization. The retention of sustainability in the context of COVID-19 pandemic uncertainty requires immediate response. Therefore, this paper addresses the following research question: how does organizational creativity contribute to managing challenges in the context of COVID-19 pandemic uncertainty as a precondition for resilience? Thus, the paper offers several contributions. First of all, the research dwells on the conceptual attributes of the learning organization: the object is identified and substantiated, the ways the learning organization’s vulnerability manifests itself through are presented; the factors creating the learning organization’s COVID-19 pandemic vulnerability are discussed; it is identified what capacities are necessary and in what learning processes they develop to reduce the learning organization’s COVID-19 pandemic vulnerability. Secondly, the paper identifies and discusses critical challenges to the learning organization caused by COVID-19 pandemic uncertainty, the ones that the organization must react to immediately to reduce its COVID-19 pandemic vulnerability: rapid social innovation cycle, expansion of organizational learning and optimisation of perceived organizational support for employee trust and commitment. Thirdly, the paper discuss how creativity is important for response.